Nanoelicitors Application Promote Antioxidant Capacity of Asparagus officinalis (In Vitro): Nanoelicitors Application Promote Antioxidant Capacity - Reza Mohammadhassan; Annahid Ferdosi; Alexander Marcus Seifalian; Maral Seifalian; Shiva Malmir (Journal of Tropical Life Science, 2021)
Nanoparticles recently play remarkable roles in modern agriculture and biotechnology due to specific exclusively physicochemical and biological characteristics of the particles. In recent years, nanoparticles are been using as fertilizers and elicitors to improve crops. Nutritionists are constantly seeking natural antioxidants without side effects to using for healthcare and treatment. Asparagus officinalis L. as medicinal plant treated by iron (0, 10, 50 and 100 mg/L) and selenium (0, 0.5,and 1 mg/L) nanoparticles as nano elicitors. Then the antioxidant capacity of A. officinalis L. was detected and measured by Î±, Î±-diphenyl-Î²-picrylhydrazyl (DPPH) assay, for assessment of the antioxidant activity. The iron nanoparticlesconcentration significantly increases the antioxidant activity of both male and female asparagus stem, as well as selenium nanoparticles. When combined iron and selenium used as nano elicitors then cause the antioxidant activity significantly decreases. But the integration of two nano elicitors (iron and selenium) decreased antioxidant capacity while the use of nano-selenium could enhance antioxidant capacity. The application of nano elicitor increased antioxidant capacity in the female stem than male.